ALLELOPATHIC POTENTIAL OF FEW TREE LEAF LEACHATES ON GERMINATION AND EARLY SEEDLING GROWTH OF PADDY - Neelamegam, Ramasamy (Journal of Phytology, 2015)
Experiments were conducted under in vitro condition to evaluate the allelopathic potential of leaf leachates (20% w/v) of three multiple use trees, Neem (Azadirachta indica), Sandal (Santalum album) Poovarasu (Thespesia populnea) on paddy (Oryza sativa L) var. ponmani. Both, fresh and dry leaf leachates of Santalum showed more promotery effect on seed germination and seedling growth parameters of paddy as compared to control and other (neem and poovarasu) leaf leachates either alone or in combination. Among the leaf leachates (fresh & dry) of multiple use trees tested on paddy, the dry leaf leachates showed more stimulatory (negative allelopathic) effect than the fresh leaf leachates.